Properties Of Kenaf Bast Powder Filled High Density Polyethylene/Ethylene Propylene Diene Rubber Composites - Saad, Anis Safinas Md (2014)
The properties of thermoplastic elastomer composites of kenaf bast powder filled HDPE/EPDM were investigated. The composites were prepared by melt blending at 70/30 phr ratio of HDPE/EPDM with different filler loading, e.g; 10, 20, 30 and 40 phr. The properties of kenaf bast powder was investigated by using X-ray diffraction (XRD), fourier tranform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). Treated kenaf bast powder from combination of chemical treatment of sodium hydroxide (NaOH) and hydrochloric acid (HCl) shows higher crystallinity index (CrI) and thermal stability as compared to untreated kenaf bast powder. The smooth surface of treated kenaf bast powder can be observed from scanning electron microscopy (SEM) after the removal of wax and reduction of lignin and hemicelluloses. From the investigation, the increasing of tensile modulus and water uptake was observed with the increasing of filler loading for all composition of composites. On the other hand, tensile strength and elongation at break decrease with increasing of filler loading. The composites also show the decreasing of thermal stability as the filler loading increased. Treated kenaf bast powder filled HDPE/EPDM composites have higher tensile strength, elongation at break, tensile modulus and low water uptake as compared to untreated kenaf bast powder filled HDPE/EPDM composites. Composites with the addition of maleic anhydride (MAH) during melt blending process shows low thermal stability and water uptake as compared to composites without MAH.